PENGARUH MOTIVASI KERJA DAN KEPUASAN KERJA TERHADAP KINERJA GURU DENGAN VARIABEL MODERASI KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH PADA SEKOLAH DASAR NEGERI UPTD DIKPORA KECAMATAN SAYUNG KABUPATEN DEMAK - Purwanto, Ignatius (Students Journal of Economic and Management, 2012)
The purpose of this study to determine: testing the effect of motivation, job satisfaction and transformational leadership role of the principal motivation moderating effect on performance, examining the influence of role principal transformational leadership moderated the effect of job satisfaction on the performance of elementary school teachers in the district Dikpora UPTD Sayung Demak Research conducted in elementary school teachers Technical Unit Department of Education, Youth and Sports Kecamtan Sayung Demak numbering 343 people scattered in 44 schools. The sampling technique used is proportional random sampling, the samples were taken by 78 teachers, observed variables are independent variable labor discipline and motivation, moderating variables that principal leadership and teacher performance dependent variable. Data analysis techniques in this study using regression analysis and hypothesis testing moderation calculation t test at significance level of 5%. The results were obtained: motivation and job statisfaction significant positive effect on teacher performance, transformational leadership has a role in strengthening the influence of motivation on teacher performance, transformational leadership has not a role in strengthening the influence of job satisfaction on the performance of teachers.. Keywords: Work motivation, job satisfaction, Leadership School head and teacher Performance